Work participation, mobility and foot symptoms in people with systemic lupus erythematosus: findings of a UK national survey - Stevens, M. J. (J Foot Ankle Res, 2019)
OBJECTIVE: The aim of this study was to investigate whether foot and lower limb related symptoms were associated with work participation and poor mobility in people with Systemic Lupus Erythematosus (SLE). METHOD: A quantitative, cross-sectional, self-reported survey design was utilised. People with SLE from six United Kingdom (UK) treatment centres and a national register were invited to complete a survey about lower limb and foot health, work participation and mobility. Data collected included work status and the prevalence of foot symptoms. The focus of the analyses was to explore potential associations between poor foot health work non-participation. RESULTS: In total, 182 useable surveys were returned. Seventy-nine respondents reported themselves as employed and 32 reported work non-participation. The remaining were retired due to age or reported work non-participation for other reasons. Work non-participation due to foot symptoms was significantly associated with difficulty walking (p = 0.024), past episodes of foot swelling (p = 0.041), and past episodes of foot ulceration (p = 0.018). There was a significant increase in foot disability scores amongst those not working (mean 18.13, 95% CI: 14.85–21.41) compared to those employed (mean 10.16, 95% CI: 8.11–12.21). CONCLUSIONS: Twenty-nine% of people with SLE reported work non-participation because of lower limb or foot problems. Our results suggest that foot health and mobility may be important contributors to a persons’ ability to remain in work and should be considered as part of a clinical assessment.